1985
DOI: 10.1007/bf01966677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various compounds on histidine decarboxylase activity: Active site mapping

Abstract: The effect of about one hundred compounds on the activity of histidine decarboxylase partially purified from whole bodies of fetal rats was determined. Most of them at their 10 mM concentration had little effect on the enzyme activity; but 12 compounds inhibited the enzyme to a greater extent than 30%. Among these, except for alpha-methylhistidine that has been known to be a strong and specific inhibitor, DOPA, homocysteine, cysteine, methionine and urocanic acid were the best inhibitors; beta-phenyllactic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This binding mode of the coenzymesubstrate conjugate in the active site of hHDC demonstrates that the imidazole binding moiety of substrate consists of a tightly packed and specific pocket in contrast to that of pDDC ( Fig. 5A-C) (38). Tyr-81B in hHDC adopted a "closed conformation" in contrast to the "open conformation" of the corresponding residue Phe-80B in pDDC and can form a stacking interaction with the imidazole ring and an additional hydrogen bond with the N1 atom of the imidazole ring (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…This binding mode of the coenzymesubstrate conjugate in the active site of hHDC demonstrates that the imidazole binding moiety of substrate consists of a tightly packed and specific pocket in contrast to that of pDDC ( Fig. 5A-C) (38). Tyr-81B in hHDC adopted a "closed conformation" in contrast to the "open conformation" of the corresponding residue Phe-80B in pDDC and can form a stacking interaction with the imidazole ring and an additional hydrogen bond with the N1 atom of the imidazole ring (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the pro-histaminic pathway is tissue-dependent. Indeed, carnosine is an inhibitor of histidine decarboxylase [131], and it has been shown that histamine release from mast cell is decreased after carnosine treatment [132]. Therefore, antioxidant and carbonyl-scavenging activity, as well as pro-histaminic properties may contribute to the effect of carnosine in different tissues under a variety of physiological and pathological conditions.…”
Section: Mechanisms Of In Vivo Action Of Carnosine: Pre-clinical Amentioning
confidence: 99%
“…Such a process occurs, for example, with preserved fish, and urocanic acid has been proposed as a spoilage index [13]. It is also known that urocanic acid is an inhibitor of histidine decarboxylase [14] and that it has specific toxicity towards certain neoplastic cells [15]. Moreover, being subjected to a ( E / Z ) photoisomerization [ 161, urocanic acid may find use to protect the human epidermis from solar radiations [ 171.…”
Section: A R = H B R = a Cmentioning
confidence: 99%